What shape do UK trainees want their training to be? Results of a cross-sectional study. Issue 10 (7th October 2016) - Harries, Rhiannon L; Rashid, Mustafa; Smitham, Peter; Vesey, Alex; McGregor, Richard; Scheeres, Karl; Bailey, Jon; Sohaib, Syed Mohammed Afzal; Prior, Matthew; Frost, Jonathan; Al-Deeb, Walid; Kugathasan, Gana; et al.
Abstract : Objectives: The British Government is acting on recommendations to overhaul postgraduate training to meet the needs of the changing population, to produce generalist doctors undergoing shorter broad-based training (Greenaway Review). Only 45 doctors in training were involved in the consultation process. This study aims to obtain a focused perspective on the proposed reforms by doctors in training from across specialities. Design: Prospective, questionnaire-based cross-sectional study. Setting/participants: Following validation, a 31-item electronic questionnaire was distributed via trainee organisations and Postgraduate Local Education and Training Board (LETB) mailing lists. Throughout the 10-week study period, the survey was publicised on several social media platforms. Results: Of the 3603 demographically representative respondents, 69% knew about proposed changes. Of the respondents, 73% expressed a desire to specialise, with 54% keen to provide general emergency cover. A small proportion (12%) stated that current training pathway length is too long, although 86% felt that it is impossible to achieve independent practitioner-level proficiency in a shorter period of time than is currently required. Opinions regarding credentialing were mixed, but tended towards disagreement. The vast majority (97%) felt credentialing should not be funded by doctors in training. Respondents preferred longer placement lengths with increasing career progression. Doctors in training value early generalised training (65%), with suggestions for further improvement. Conclusions: This is the first large-scale cross-specialty study regarding the Shape of Training Review. Although there are recommendations which trainees support, it is clear that one size does not fit all. Most trainees are keen to provide a specialist service on an emergency generalist background. Credentialing is a contentious issue; however, we believe removing aspects from curricula into post-Certificate of Completion of Training (CCT) credentialing programmes with shortened specialty training routes only degrades the current consultant expertise, and does not serve the population. Educational needs, not political winds, should drive changes in postgraduate medical education and all stakeholders should be involved.